2011
DOI: 10.1007/s11001-011-9116-2
|View full text |Cite|
|
Sign up to set email alerts
|

Sediment identification using free fall penetrometer acceleration-time histories

Abstract: Knowledge of physical properties of near-surface sediments is an important requirement for many studies of the seafloor. Dynamic or Free Fall Penetrometers (FFP), instrumented with accelerometers, are widely used to assess the mechanical properties of the sediment by deriving penetration resistance from the deceleration response of the probe as it impacts and embeds the seabed. Other field investigations, a priori knowledge or a very basic description of the type of sediment (such as a description of the sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…Theoretical studies have shown the difficulties in correlating v 0 with the state of consolidation and z depth (e.g., Boguslavskii et al 1996). Similar to the results from Mulukutla et al (2011), our data show a direct correlation between v 0 and z depth (Fig. 12).…”
Section: Correlation Of Penetration Depth To Initial Penetration Ratesupporting
confidence: 82%
See 2 more Smart Citations
“…Theoretical studies have shown the difficulties in correlating v 0 with the state of consolidation and z depth (e.g., Boguslavskii et al 1996). Similar to the results from Mulukutla et al (2011), our data show a direct correlation between v 0 and z depth (Fig. 12).…”
Section: Correlation Of Penetration Depth To Initial Penetration Ratesupporting
confidence: 82%
“…However, both models demonstrate that an increase in z depth correlates directly to a reducing state of consolidation or firmness factor (Fig. 12, Mulukutla et al 2011).…”
Section: Correlation Of Penetration Depth To Initial Penetration Ratementioning
confidence: 95%
See 1 more Smart Citation
“…In Yakutat Bay, 50 deployments achieved an impact velocity within the range used by Mulukutla et al () for classification using FF. For the deployments with FF = 10.5–70 m −1 , the maximum deceleration ranged between 31.5 and 70 g .…”
Section: Resultsmentioning
confidence: 83%
“…They found that the presence of coarse‐grained sediments led to decelerations of more than 60 g , while decelerations of less than 20 g were measured in areas of soft clay. Mulukutla et al () proposed the Firmness Factor (FF) to characterize sediments based on penetrometer deceleration records: normalFnormalF = amaxvi g tp where a max is maximum acceleration, v i is impact velocity, and t p is the total penetration time. The minimum values of FF for fine sand and maximum for coarse silt ranged between 10.5 and 70 m −1 for an impact velocity between 4.86 and 9.16 m/s.…”
Section: Methodsmentioning
confidence: 99%